Digit Sucking Habit and Association with Dental Caries and Oral Hygiene Status of Children Aged 6 Months to 12 Years Resident in Semi-Urban Nigeria - Kikelomo Adebanke Kolawole; Morenike Oluwatoyin Folayan; Hakeem Olatunde Agbaje; Titus Ayodeji Oyedele; Elizabeth Obhioneh Oziegbe; Nneka Kate Onyejaka; Nneka Maureen Chukwumah; Olusegun Victor Oshomoji (Cross Mark, 2024)
14p